DYNAMICS OF FREEING OF WHITE STREPTOTSID FROM POLYMERIC MEDICAL TAPE - Мельник, М. В.; Попадюк, О. Я.; Геник, С. М.; Мельник, Д. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The general method of exposure of sulfanilamid preparations is adapted to the quantitative control of exposure of white streptotsid that frees oneself from polymeric medical tape. A method is developed with the use of butanol for extraction of formed in the reaction of dye.